Cost-effectiveness of the third-agent class in treatment-naive human immunodeficiency virus-infected patients in Portugal. - Filipa Aragão (Public Library of Science (PLoS), 2012)
Introduction Current Portuguese HIV treatment guidelines recommend initiating antiretroviral therapy with a regimen composed of two Nucleoside Reverse Transcriptase Inhibitors plus one Non-nucleoside Reverse Transcriptase Inhibitor (2NRTI+NNRTI) or two Nucleoside Reverse Transcriptase Inhibitors plus one boosted protease inhibitor (2NRTI+PI/r). Given the lower daily cost of NNRTI as the third agent when compared to the average daily costs of PI/r, it is relevant to estimate the long term impact of each treatment option in the Portuguese context. Methods We developed a microsimulation discrete events model for cost-effectiveness analysis of HIV treatment, simulating individual paths from ART initiation to death. Four driving forces determine the course of events: CD4+ cell count, viral load, resistance and adherence. Distributions of time to event are conditional to individuals' characteristics and past history. Time to event was modeled using parametric survival analysis using Stata 11®. Disease progression was structured according to therapy lines and the model was parameterized with cohort Portuguese observational data. All resources were valued at 2009 prices. The National Health Service's perspective was assumed considering a lifetime horizon and a 5% annual discount rate. Results In this analysis, initiating therapy with two Nucleoside Reverse Transcriptase Inhibitors plus one Non-nucleoside Reverse Transcriptase Inhibitor reduces the average number of switches by 17%, saves 19.573€ per individual and increases life expectancy by 1.7 months showing to be a dominant strategy in 57% of the simulations when compared to two Nucleoside Reverse Transcriptase Inhibitors plus one boosted protease inhibitor. Conclusion This study suggests that, when clinically valid, initiating therapy with two Nucleoside Reverse Transcriptase Inhibitors plus one Non-nucleoside Reverse Transcriptase Inhibitor is a cost-saving strategy and equally effective when compared to two Nucleoside Reverse Transcriptase Inhibitors plus one boosted protease inhibitor as the first regimen.